Chapter 11 - Dynamics and innovative technologies affecting diets: implications on global food and nutrition security - Descalzo, Adriana Maria; Pighin, Darío Gabriel; Dhuique-Mayer, Claudie; Lorenzo, José Manuel; Grigioni, Gabriela Maria (Elsevier, 2021)
Consumers are increasingly aware of the influence of diet on their health and require products that contribute to their well-being. The food security concept requires increased knowledge about minor components in the diet as micronutrients, vitamins, bioactive compounds together with fatty acids, which are naturally present in food and exert biological effects to improve human health. This chapter provides an insight into the physiological function of the body and the biochemical function of the fatty acids and polar lipids. It discusses the significance of health-related fatty acids, their presence in food and consumption, and how all these factors help in achieving food and nutrition security. In addition, an approach to some food processing and preservation technologies is presented.